2018
DOI: 10.1177/0269215518793483
|View full text |Cite
|
Sign up to set email alerts
|

How is sexuality after stroke experienced by stroke survivors and partners of stroke survivors? A systematic review of qualitative studies

Abstract: Stroke has a profound impact on how sexuality is experienced by both stroke survivors and partners of stroke survivors. Despite this, post-stroke sexuality is rarely discussed openly. Stroke survivors and partners value sexuality and may benefit from strategies to support adjustment to post-stroke sexuality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 51 publications
2
61
1
Order By: Relevance
“…In a qualitative study Martinsen et al (26) have shown the vulnerable situation for persons with stroke, in particular singles. In light of the present results, and in accordance with McGrath et al (15), it seems important to include spouses when addressing post-stroke recovery, as the spouses are at risk of a life in an unsatisfying partner relationship.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In a qualitative study Martinsen et al (26) have shown the vulnerable situation for persons with stroke, in particular singles. In light of the present results, and in accordance with McGrath et al (15), it seems important to include spouses when addressing post-stroke recovery, as the spouses are at risk of a life in an unsatisfying partner relationship.…”
Section: Discussionsupporting
confidence: 89%
“…Negative changes in family roles and partner roles are commonly reported both among those who have had a stroke and their spouses (12,15,(25)(26)(27)(28)(29)(30) and can be an important explanation for the low levels of satisfaction with "Family life" and "Partner relationship" 6 years after stroke. Unwanted role changes within a partner relationship, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S troke has a profound impact on the ways in which sexuality is experienced and expressed by stroke survivors and their partners. A recent thematic synthesis found that, while sexuality is largely silenced by stroke, it nonetheless remains important to stroke survivors and their partners (1). International clinical guidelines for stroke rehabilitation propose that sexuality should be included as a core component of comprehensive rehabilitation (2)(3)(4).…”
mentioning
confidence: 99%